2004
DOI: 10.1089/pho.2004.22.298
|View full text |Cite
|
Sign up to set email alerts
|

Laser-Assisted End-to-End Vascular Anastomosis of Elastin Heterograft to Carotid Artery with an Albumin Stent in Vivo

Abstract: Laser-assisted vascular anastomosis of elastin heterograft to medium size vessel is possible. Albumin stent played an important role in strength of the anastomosis. Chronic studies are warranted to determine long-term patency and histology of the laser-assisted vascular anastomosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…By employing the ''fold and bond'' technique, we have been able to reduce the amount of laser energy required to form a stable anastomosis. This was achieved by delivering approximately 120 J of laser energy per completed anastomosis, compared to the 212 J required to achieve the same endstate in a similar sized porcine arterial model [22] at an output power approximately 30% of that described as optimal by Ren et al [23]. As energy is delivered to the target tissue, the ICG dye within the BioWeld 1 solder causes preferential absorption of the laser.…”
Section: Discussionmentioning
confidence: 99%
“…By employing the ''fold and bond'' technique, we have been able to reduce the amount of laser energy required to form a stable anastomosis. This was achieved by delivering approximately 120 J of laser energy per completed anastomosis, compared to the 212 J required to achieve the same endstate in a similar sized porcine arterial model [22] at an output power approximately 30% of that described as optimal by Ren et al [23]. As energy is delivered to the target tissue, the ICG dye within the BioWeld 1 solder causes preferential absorption of the laser.…”
Section: Discussionmentioning
confidence: 99%
“…Recent research has evaluated the ability of chemical materials, such as glues and/or dyes, to increase laser absorption and thus improve tissue welding strength . Most in vivo studies have used stay sutures , to approximate both edges of vessel segments and to increase tension.…”
Section: Introductionmentioning
confidence: 99%
“…Pushing the sample towards the coapted tissue end prior to irradiation may avoid tissue separation during laser irradiation. A review paper published in 2004 identified 37 relevant studies of LAVA/LAVR , and we found additional 31 relevant studies published mainly after 2004 . Of these 68 studies, 26 evaluated LAVA/LAVR without stay sutures .…”
Section: Introductionmentioning
confidence: 99%
“…Most researchers do not incorporate temperature control in their LTB system. They usually apply a constant laser power and the tissue reaches some steady-state temperature (which is unknown, and can only be estimated in some of the cases) [15][16][17][18]. The few researchers who did use temperature control in their system heated abruptly the bonded surface to a desired temperature, T set .…”
Section: Introductionmentioning
confidence: 99%
“…The temperature rise resembled a ''step'' function, whose rise time was roughly 3-4 seconds. Once the settemperature, T set , was reached, the heated spot was either kept at that temperature for some predetermined dwell time, or was slowly translated along the cut at a constant rate [14][15][16][17][18][19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%